Process-independent quantitative assessment of residual biological contamination of medical devices reprocessed in washer-disinfectors - Sigler, K; Chládková, K; Vacata, V; Gebel, J; Gásková, D (Folia microbiologica, 2005)
A method based on measuring a soil-induced fluorescence intensity response of 1,8-anilinonaphthalene sulfonate at two fixed wavelengths (460 and 510 nm) was used for determining residual contamination on test soil carriers simulating medical devices after passage through a hospital washer-disinfector. The fluorescence response can be satisfactorily calibrated to soil levels as low as approximately 1 microg/L. Practical tests were performed in two hospitals with washer-disinfectors of 3 types and with several chemical or enzymic cleansers-disinfectants. In combination with the previously developed system of standardized test soil carriers simulating both easily and poorly accessible parts of soiled medical devices, the liver-lactose-oil test soil and an efficient sonication procedure for stripping the residual soil off the carriers, this soil detection method permits the detection of very low contamination levels.
Keywords: infekce spojené se zdravotní péčí; kontaminace zdravotnického vybavení; Equipment Reuse; opakované použití vybavení; dezinfekce; půda; Evropská unie; Humans; Disinfection; Soil; Soil Microbiology; lidé; Equipment Contamination; půdní mikrobiologie; European Union; Cross Infection